Nicotinamide polymeric nanoemulsified systems: a quality-by-design case study for a sustained antimicrobial activity - Zidan AS (Dove Medical Press, 2016)
Ahmed S Zidan,1,2 Osama AA Ahmed,1,3 Bader M Aljaeid1 1Department of Pharmaceutics and Industrial Pharmacy, Faculty of Pharmacy, King Abdulaziz University, Jeddah, Kingdom of Saudi Arabia; 2Department of Pharmaceutics and Industrial Pharmacy, Faculty of Pharmacy, Zagazig University, Zagazig, 3Department of Pharmaceutics and Industrial Pharmacy, Faculty of Pharmacy, Minia University, Minia, Egypt Abstract: Nicotinamide, the amide form of vitamin B3, was demonstrated to combat some of the antibiotic-resistant infections that are increasingly common around the world. The objective of this study was to thoroughly understand the formulation and process variabilities affecting the preparation of nicotinamide-loaded polymeric nanoemulsified particles. The quality target product profile and critical quality attributes of the proposed product were presented. Plackett–Burman screening design was employed to screen eight variables for their influences on the formulation’s critical characteristics. The formulations were prepared by an oil-in-water emulsification followed by solvent replacement. The prepared systems were characterized by entrapment capacity (EC), entrapment efficiency (EE), particle size, polydispersity index, zeta potential, transmission electron microscopy, Fourier transform infrared spectroscopy, differential scanning calorimetry, powder X-ray diffraction, in vitro drug release, and their antibacterial activity against bacterial scrums. EC, EE, particle size, polydispersity index, zeta potential, and percentage release in 24 hours were found to be in the range of 33.5%–68.8%, 53.1%–67.1%, 43.3–243.3 nm, 0.08–0.28, 9.5–53.3 mV, and 5.8%–22.4%, respectively. One-way analysis of variance and Pareto charts revealed that the experimental loadings of 2-hydroxypropyl-β-cyclodextrin and Eudragit® S100 were the most significant for their effects on nicotinamide EC and EE. Moreover, the polymeric nanoemulsified particles demonstrated a sustained release profile for nicotinamide. The Fourier transform infrared spectroscopy, differential scanning calorimetry, and X-ray diffraction demonstrated a significant interaction between the drug and 2-hydroxypropyl-β-cyclodextrin that might modulate the sustained release behavior. Furthermore, the formulations provided a sustained antibacterial activity that depended on nicotinamide-loading concentration, release rate, and incubation time. In conclusion, the study demonstrated the potential of polymeric nanoemulsified system to sustain the release and antibacterial activity of nicotinamide. Keywords: nicotinamide, polymeric nanoemulsified systems, Plackett–Burman design, antibacterial activity, sustained release